A rossz magyar egészségi állapot lehetséges magyarázó tényezői; összehasonlító makroelemzés magyar és osztrák adatok alapján, 1960 - 2004 - Mária Lackó (Hungarian Academy of Sciences, Institute of Economics, 2010)
– In Hungary, the health status of working age men is extremely bad in comparison with both the developed market economies and the neighboring transition countries. The study based on data between 1960 and 2004 investigates the health status of population in Hungary and Austria by health-production functions on macro level and makes comparisons. The rationale for comparison of these very countries is the territorial closeness and the mutual long past. The mortality rate of working age population (15-60 old) is considered the proxy variable for the health status. According to this indicator the health status in the two countries was at the same level in 1960's, but they started to diverge at the beginning in the 1970's. As explanatory variables for the mortality rate of the working age population the following variables are taken into account: the indicators of the life style (consumption of alcohol, smoking, the extra work in the "second" and "hidden economy"), the long- term economic development (the development of the GDP per capita), health-care resources (the relative share of physicians) and the situation in the labor market (unemployment rate). The estimations of the health production functions turn out approximating well real world developments in both countries.
Keywords: I12; 330; health status; health production function; mortality; Hungary; Austria; Gesundheit; Gesundheitsökonomik; Produktionsfunktion; Sterblichkeit; Schätzung; Vergleich; Ungarn; Österreich